2018
DOI: 10.3892/etm.2018.5716
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR-766-5p in cell migration and invasion in colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) develops from the colon or rectum and is the fourth highest inducer of cancer mortality. In the present study, cancer tissues and normal tissues were extracted from patients with CRC who were treated in the Affiliated Hospital of Shandong University of Traditional Chinese Medicine (Jinan, China). Reverse transcription-quantitative polymerase chain reaction demonstrated that the expression level of miR-766-5p was significantly higher (P<0.01) in cancer tissue than that in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…These data collectively suggest an antagonistic role of miR-766-5p and CASC15 on each other. A similar antagonistic role of miR-766-5p was observed by Jia et al in colorectal cancer where they showed that miR-766-5p inhibitor repressed the process of colorectal cancer by targeting suppressor of cancer cell invasion (SCAI) [26]. Wang et al found that miR-766 could serve as a novel p53 activator which functioned by targeting MDM4 and thereby enhancing the p53 signaling axis [27].…”
Section: Discussionsupporting
confidence: 58%
“…These data collectively suggest an antagonistic role of miR-766-5p and CASC15 on each other. A similar antagonistic role of miR-766-5p was observed by Jia et al in colorectal cancer where they showed that miR-766-5p inhibitor repressed the process of colorectal cancer by targeting suppressor of cancer cell invasion (SCAI) [26]. Wang et al found that miR-766 could serve as a novel p53 activator which functioned by targeting MDM4 and thereby enhancing the p53 signaling axis [27].…”
Section: Discussionsupporting
confidence: 58%
“…Jia et al found that miR-766 expression was increased in colorectal cancer and could function as an oncogene. 28 Similarly, Li et al demonstrated that miR-766 promoted cell proliferation of human colorectal cancer by inhibiting the expression of SOX6. 29 However, the expression status and biological function of miR-766 in OS are largely unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Wistar rats weighing 220-250 g and aged 10-12 weeks old were purchased from The Animal Centre of Nanchang University (Nanchang, China) and housed in our laboratory at 22-23˚C in 55-60% humidity, with a 12 h light/dark cycle, and free access to food and water. The rats underwent urinary bladder massage at least twice per day until the recovery of spontaneous micturition (9). The present study was approved by the Research Council and Animal Care and Use Committee of Shangrao People's Hospital (Shangrao, China), and performed according to the National Institutes of Health Guide for the Care and Use of Laboratory Animals (9).…”
Section: Animals and Spinal Cord Surgery A Total Of 12 Malementioning
confidence: 99%
“…The rats underwent urinary bladder massage at least twice per day until the recovery of spontaneous micturition (9). The present study was approved by the Research Council and Animal Care and Use Committee of Shangrao People's Hospital (Shangrao, China), and performed according to the National Institutes of Health Guide for the Care and Use of Laboratory Animals (9). Rats were randomly divided into two groups: Control (n=6) and SCI model (n=6).…”
Section: Animals and Spinal Cord Surgery A Total Of 12 Malementioning
confidence: 99%